The Implementation of the Hungarian Numerus Clausus Act at the University of Pécs in the 1920s - Paksy, Zoltán (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2020)
On 22 September 1920 the Hungarian National Assembly passed a law called the “Act on the regulation of admission to the universities of arts and sciences, the University of Technology, the University of Budapest Faculty of Economics and Academies of law”, or as it is widely known, the numerus clausus law. This restricted the rate of Jews in the population and Jewish students at universities to 6% in Hungary. The leaders of the university of Pécs interpreted the numerus clausus law in a different way than the leaders of Pázmány Péter University in Budapest, so more Jewish students were able to study at the University of Pécs than it was allowed. Christian students protested that and came to blow, but the leadership of the university pacified the situation, and they sabotaged the execution of the law by taking advantage (for the greater good) of the legal loopholes and opportunities offered by bad legislation.